WAYS TO IMPROVE TRANSPORT INFRASTRUCTURE FOR SUSTAINABLE DEVELOPMENT OF THE REGIONAL ECONOMY (Universal International Scientific Journal, 2026)
This article discusses ways to improve transport infrastructure for the sustainable development of the regional economy. It also provides conclusions and suggestions for improving transport infrastructure in the regional economy.
Keywords: Region; regional economy; transport